1995
DOI: 10.1175/1520-0477(1995)076<1801:eoccod>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cumulus Clouds over Deforested Lands in Amazonia

Abstract: A survey of shallow (fair weather) cumulus clouds over part of Amazonia yields evidence of enhanced frequency where the forest had been cleared. The survey covers one dry-season month from 1988. It employs a threshold algorithm to construct an image of cumulus cloud cover from sets of geostationary satellite visible-infrared image pairs. Cumulus images were constructed for two times. The morning image shows no association of the cumulus index with cultural features. However, in the afternoon image a patch of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 12 publications
10
63
0
4
Order By: Relevance
“…Even though the development of clouds (shallow or deep) at a certain location sometimes has little to do with land cover and its contrast, e.g., due to synoptic frontal systems, the signal of clouds-landcover coupling represented by the well separated P( ͉N,n) is unambiguous for both types of clouds. This result confirms the earlier findings (13,19). The physical mechanisms responsible for the observed surface dependent convection on CDD counts are discussed next.…”
Section: Statistical Analysis Of Shallow and Deep Cloudssupporting
confidence: 93%
See 1 more Smart Citation
“…Even though the development of clouds (shallow or deep) at a certain location sometimes has little to do with land cover and its contrast, e.g., due to synoptic frontal systems, the signal of clouds-landcover coupling represented by the well separated P( ͉N,n) is unambiguous for both types of clouds. This result confirms the earlier findings (13,19). The physical mechanisms responsible for the observed surface dependent convection on CDD counts are discussed next.…”
Section: Statistical Analysis Of Shallow and Deep Cloudssupporting
confidence: 93%
“…Images from multiple satellites hint at a correspondence between the patterns of clouds and those of land cover over some partially deforested regions (4,12,13), in particular over the study domain of this analysis in Rondonia (500 ϫ 500 km 2 in size centered at 62.5°W and 10.5°S shown in Fig. 1 Left).…”
mentioning
confidence: 64%
“…Extensive areas of native forests within the state of Rondônia (in the southwestern part of Brazilian Amazonia) have been extensively replaced by pastures (Skole and Tucker, 1993), making it one of the sites of application of such gridded models. Especially in the dry season, it has been noted that the interaction between mesoscale circulations induced by land-surface heterogeneities and the large-scale flow may enhance and deepen the convective activity over disturbed areas , in agreement with cloud cover surveys performed by Cutrim et al (1995). During the rainy season, however, deforestation in Rondônia does not seem to have a significant effect on the distribution of cloudiness and rainfall, since the synoptic conditions tend to be propitious to induce mesoscale circulations alone (Wang et al, 2000), in agreement with the satellite images evaluated by Laurent et al (2002).…”
Section: Mesoscale Modelssupporting
confidence: 78%
“…Convective activity is strongly influenced by surface characteristics, with changes in land cover producing changes in local surface temperatures and precipitation rates. From satellite observations Rabin et al [1990] and Cutrim et al [1995] reported increased cloudiness over deforested areas in Amazonia and attributed this to land surface heterogeneity. Using GOES (Geostationary Operational Environmental Satellite), TRMM (Tropical Rainfall Measuring Mission) and Special Sensor Microwave Imager (SSM/I) satellite data, Negri et al [2004] found that enhanced dry season surface heating created a thermal circulation which increased shallow cumulus clouds, and the precipitation resulting from deep convection over deforested relative to those over forested regions in Amazonia.…”
Section: Impact Of Deforestation On Regional Hydrometeorologymentioning
confidence: 99%